ChemInform Abstract: Intramolecular Insertions into Unactivated C(sp3)—H Bonds by Oxidatively Generated β‐Diketone‐α‐Gold Carbenes: Synthesis of Cyclopentanones. Issue 38 (3rd September 2015) - Wang, Youliang; Zheng, Zhitong; Zhang, Liming
Abstract For the first time, oxidatively generated β‐diketone‐α‐gold carbenes are intramolecularly inserted into unactivated C(sp3)—H bonds using ynones as substrates.